Form Without Function: The Missing Creative Element in Telangana's Grammar Pedagogy - Srinivas, Revathi (Journal of English Language Teaching and Applied Linguistics, 2025)
Grammar instruction plays a crucial role in language learning, serving as a fundamental component of English language education in schools worldwide. Despite the acknowledged importance of balanced language teaching approaches, the methods and activities used to teach grammar remain a subject of ongoing pedagogical research and debate. In the context of Telangana's government school system, understanding the nature and distribution of grammar activities within English textbooks becomes particularly significant for evaluating the effectiveness of current language teaching strategies. This study examined grammar activities in English textbooks prescribed for Classes I–X in government schools of Telangana, India. Using Baleghizadeh’s (2012) framework—which categorizes grammar activities based on accuracy/fluency orientation and reproductive/creative characteristics—the research analyzed 177 grammar activities across ten textbooks. Results revealed a significant imbalance, with 89.3% of activities classified as accuracy-centered reproductive activities, 10.7% as fluency-centered reproductive activities, and a complete absence of creative grammar activities. This skewed distribution contradicts contemporary language teaching approaches that advocate for a balance between explicit grammar instruction and communicative, task-based practice. The study concludes with recommendations for textbook developers to integrate more fluency-centered and creative activities to enhance learners’ grammatical competence in authentic communicative contexts.